(untitled) (World Bulletin of Public Health, 2025)
Cystic fibrosis is a genetic disorder caused by mutations in the CFTR gene. This autosomal recessive disorder is diagnosed in many regions by newborn screening, while in other regions, diagnosis is based on a cluster of recognized multiorgan clinical manifestations, elevated sweat chloride concentrations, or CFTR mutations. Cystic fibrosis is often associated with a shortened life expectancy, and the most common cause of death is endstage lung disease